Facile preparation of thermoplastic elastomer with high service temperature from dry selective curing of compatibilized EPDM/polyamide-12 blends. (May 2015) - Jung, Hyo Shin; Choi, Myung Chan; Chang, Young-Wook; Kang, Phil-Hyun; Hong, Sung Chul
Graphical abstract: Highlights: A facile preparation of thermoplastic elastomer (TPE) is demonstrated. The TPE is prepared through a melt-mixing of commercially available resource. Eco-friendly e-beam irradiation is applied for the selective dry curing of the TPE. The TPE exhibits high service temperature of up to ∼180 °C. The TPE shows excellent reprocessing capability and good mechanical properties. Abstract: A facile preparation of thermoplastic elastomer (TPE) from simple polymer blends, elastically reinforced through a dry curing process, is introduced in this study. A TPE with a high service temperature of up to ∼180 °C is prepared by melt mixing ethylene–propylene–diene rubber (EPDM) with polyamide-12 in the presence of maleated EPDM as a compatibilizer. A dry curing process employing electron beam (e-beam) irradiation is then applied for the selective cross-linking of the EPDM components, which is confirmed by the gel content and differential scanning calorimetry measurements. The mechanical and elastic properties of the TPE are improved by the e-beam irradiation, as evidenced by the measurements of tensile strength, elongation at break, Young's modulus and tension set, affording a tough TPE. Repeated thermal recycling of the TPE demonstrates an excellent reprocessing capability, affording environmentally friendly TPEs using commercially available resources.